Prevalence of Acute Kidney Injury (AKI) in Extremely Low Gestational Age Neonates (ELGAN) - Askenazi, David J. (Pediatr Nephrol, 2020)
BACKGROUND: To determine the prevalence and severity of acute kidney injury (AKI) at different time frames in relation to gestational age (GA) and birthweight (BW) in extremely low gestational age neonates (ELGAN). Our hypothesis is that ELGAN with lower GA and lower BW have higher AKI rates. METHODS: 923 ELGAN enrolled in the Preterm Erythropoietin Neuroprotection Trial were evaluated from birth until death or hospital discharge. AKI was defined according to kidney disease: improving global outcomes (KDIGO) definition from clinically-derived serum creatinine (SCr) measurements. Severe AKI was defined as stage 2 or higher. RESULTS: For the entire cohort, 351/923 (38.0%, CI = 34.8–41.3%) had at least one episode of stage 1 or higher AKI and 168/923 (18.2%, CI = 15.7–20.7%) had at least one episode of severe (stage 2 or higher) AKI. The prevalence of AKI stage 1 or higher for the entire cohort during the early (days 3–7), middle (days 8–14) and late follow-up period (after day 14) was 112/923 (12.1%, CI = 10.0–14.3%), 142/891 (15.9%, CI = 13.5–18.4%) and 249/875 (28.5%, CI = 25.4–31.5%), respectively. The rates of severe AKI during the hospital course were 27.8%, 21.9%, 13.6%, and 9.4% for the 24, 25, 26 and 27 week GA groups respectively. AKI rates were significantly higher with decreasing GA and decreasing BW for stated time trends (all p < 0.01 using tests for trend). CONCLUSIONS: AKI is relatively common in ELGAN during their initial hospital course, and is associated with lower GA and BW.